Corticosteroid Induced Cushing’s Syndrome - Priyanka, Bogireddy Bindu; Prasanna, D Guru; Krupa, S.; Sreenivasulu, B. (Indian Journal of Pharmacy Practice)
Corticosteroids are the drugs that are used commonly now a days as pain relievers, but these corticosteroids can affect the own immune system by suppressing. So, corticosteroids are the one of the reason for occurrence of the life threatening infectious diseases. Chronic use of corticosteroids mainly induces Cushing’s syndrome, osteoporosis, diabetes mellitus, tuberculosis, jaundice etc. In this study we discussed on case studies regarding steroid induced Cushing syndrome who are admitted in the general medicine department at Santhiram Medical College and General Hospital in Nandyal Region. In these cases, the patients had followed the treatment of corticosteroids without any doctor prescription. Prescribing of steroids by RMP’s and community pharmacies is increasing day by day, hence as role of clinical pharmacist it is advisable to create awareness on usage of steroids to the local pharmacies and RMP’s by better training on the management of steroid therapy.
Keywords: Corticosteroids; Cushing’s syndrome; RMP; Clinical pharmacist; Management.